2003
DOI: 10.1017/s0950268803008768
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiology of mumps in western Europe

Abstract: SUMMARYSix countries (Denmark, England and Wales, France, Germany, Italy and the Netherlands) conducted large serological surveys for mumps, in the mid-1990s, as part of the European Sero-Epidemiology Network (ESEN). The assay results were standardized and related to the schedules and coverage of the immunization programmes and the reported incidence of mumps. Low incidence of disease and few susceptibles amongst adolescents and young adults was observed in countries with high mumps vaccine coverage (e.g. the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 23 publications
1
19
0
3
Order By: Relevance
“…Thus, seroprevalence of IgG antibodies is central to the determination of herd immunity in a population. The level of immunity required to achieve herd immunity is 85% to 90% (12). In this study seroprevalence, as determined by the Microimmune assay, was at an acceptable level in all age groups from the 7-to 11-year group up.…”
Section: Discussionmentioning
confidence: 50%
“…Thus, seroprevalence of IgG antibodies is central to the determination of herd immunity in a population. The level of immunity required to achieve herd immunity is 85% to 90% (12). In this study seroprevalence, as determined by the Microimmune assay, was at an acceptable level in all age groups from the 7-to 11-year group up.…”
Section: Discussionmentioning
confidence: 50%
“…In the last outbreaks reported in European countries, including Italian adolescents, young adults were particularly affected by measles, because most of the population was unvaccinated or incompletely vaccinated Andrews et al 2008;Nardone et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The herd immunity for mumps is estimated at about 75-86% (Donaghy et al 2006), and the theoretical level of antibodies required to interrupt the transmission of mumps is estimated to be between 85% and 90% (Nardone et al 2003). Although asymptomatic mumps infections may be more common especially in adults (Sartorius et al 2005), the last epidemic peak in the province of Frosinone reported 137 cases with a median patient age of 7 vs. 285 cases with (Langiano et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In Deutschland geht man davon aus, dass in der Altersgruppe der über 20-jährigen bei Mumps eine Seropositivität von 93-96% erreicht wird [9]. Allerdings zeigte eine kürzliche Untersuchung des Gesundheitsamtes Mün-ster [10] …”
Section: Diskussionunclassified